Wind generation applied to water desalination and H2 production in remote areas with weak networks - Cendoya, Marcelo Gustavo (2014)
In this article are proposed the topology, the operation and the control strategy of a system for the provision of potable water and fuel production (H2) in remote areas, which is powered by a wind turbine and it is based on the concept of Renewable Distributed Generation. The system has a modular structure and comprises a Wind Generator, a Power Fluctuations Compensator, a Reverse Osmosis Desalination System and an Alkaline Electrolyser. All of these modules are interconnected through power electronic converters by an AC local bus, which in turn is linked to a pre-existing weak electrical grid. The complete system requires only an “assistance function” from the grid, using its voltage and frequency. Also, some reactive power is taken, as well as a small amount of active power to ensuring a minimum production of water and hydrogen when the wind resource is insufficient. Both, the selected operation mode and the control strategy used, allow achieving a maximum level of generated power and smoothing its fluctuations. This is done to prevent worsening the quality of potable water and the hydrogen produced, and to minimize the introduction of disturbances to the weak electrical grid. The work is completed with the computer simulation of the operation and control strategies. The obtained results are promising and fully validate the proposal.